A comparison of fundraising methods used for the Olympic Games and Chinese synthetic games - Li, S.; Wang, B. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This paper investigates and analyzes fundraising methods for national games and city games in the People`s Republic of China, and compares these to the methods used for the Olympic Games. This investigation will provide valuable theoretical basis and practical guidance for the social and economical performance of large-scale synthetic games in China. Methods Literature review was used as the research basis for this study. Data regarding fundraising methods for the national games and city games in China were collected. These data were analyzed comparatively in terms of the theories of management, economics, marketing, and sports competition. Results The primary purpose for the Olympic Games` fundraising, was to unify the Olympic image and its spirit. This spirit encompasses solidarity, friendship, and peace, which through the Olympic Games, can spread to each corner of the world, thus making the Olympic Games an intangible and appreciated asset. Currently, the Olympic Games programme and the sale of broadcasting rights are the main sources of the International Olympic Committee`s (IOC) revenue, as opposed to the funds of government economic support and society donations required for synthetic games. Further, fundraising has become a complex market-oriented operation that classifies categories and tiers of marketing modes. This highly-organised marketing network has spread internationally, which is also in contrast to the initial, dispersed, disordered business activities of synthetic games in China. When compared to fundraising methods for the Olympic Games, large-scale synthetic games in China are similar in their property and outlets. However, through analysis of the actual operation process and its results, it is evident that the Olympic Games have numerous advantages. Firstly, the whole Olympic operation classifies categories and tiers of marketing modes. The IOC determines a master plan and its organizing committee, the national Olympic committee and intermediary organizations participate accordingly. These participants explore global marketing according to the region, and distribute finances proportionately. In China, because of the absence of a permanent organization for the fundraising of large-scale synthetic games, an organizing committee is the only party who may control fundraising for such games, and this control usually is short-term. Secondly, the Olympic Games demonstrate superior professional marketing skills, through its attentiveness to professionals in economy, law and dissemination. This is also demonstrated through the cooperation with the intermediary organizations observed in Olympic Games fundraising, and the standardization of market behavior. In China, market development staff primarily have backgrounds in sport or government. There is a lack of cooperation with intermediary organizations, and operational rules are inconsistent. Finally, the IOC demonstrate superior brand strategy to large-scale synthetic games organizers in China. When the IOC marketing plan is carried out, the number of sponsors will be reduced, hence raising their status and placing emphasis on their exclusive position. In synthetic games in China, organizers often pursue quantity of sponsors and ignore quality. Hence, a remarkable differences exist between the Olympic Games and Chinese synthetic games fundraising methods. Discussion Fundraising through marketing, has ensured the independence of the Olympic organization not only in economy, but also in its ability to promote global development of the Olympic Games. Its fundraising success may be attributed to: - adjustments for exterior conditional variety, changing ideas; - development of the Olympics business value according to the market regulation of cultural products; - brand-promotion strategy; - inclusion of professional organization and personnel; - use of the global sports network for business. Consequently, it is evident that changing ideas an d developing a long-term mechanism of a commercial fundraising mode may be ideal for the promotion of large-scale synthetic games in China.